Enfoque CTS no livro didático de geografia na educação prisional a distância - Cardozo, Eduardo de Lara (2019)
Considered as a tool to support the teaching process learning the textbook in many cases, it becomes the only source of information easily accessible and available to students and teachers. However, within this intentionality you can check some books bring in its organizational structure limiting factors for certain content. These factors somehow can go unnoticed in everyday life of the teacher. There was thus sought to analyze the contribution of present exercises in the textbook of Geography in the formation of incarcerated students, with a focus on Science, Technology and Society (STS). Therefore, to achieve this objective, this paper was guided in the textbook of Geography Walk and Turn (FTD, 2013).The light of the proposed aim, this study focused on the basic principles of the inductive method, qualitative approach having as parameter the determining of a document search centered on a case study. The studied population was composed of two groups: the first consists of 14 imprisoned students enrolled in geography subject in 2018, in phase II of elementary school, the EJA mode, combined with the Distance Education (DE) linked structure educational Center for Basic Education for Youth and Adults (CEEBJA) Teacher Odair Pasqualini, located in Ponta Grossa-PR. The second group studied was made up of eight teachers of Geography discipline, working in the prison system of the state of Paraná, six teachers working in prisons CEEBJA distributed in the state, a total of nine prison CEEBJA, and two teachers linked to the Center socioeducation (CENSE), located in the city of Ponta Grossa. As a means of increasing the acquisition of data for analysis, in order to understand the involvement of the subjects involved, the data collection was based on the analysis of words derived from Science, Technology and Society (STS), present in the textbook exercises now analyzed. Beyond this time, we also used a semi-structured questionnaire with ten multiple-choice questions on STS and Scientific and Technological Literacy (ACT), as well as application of 16 selected exercises of the textbook directed to students. With regard to the field of Geography teachers, a questionnaire was applied with ten multiple choice questions proposed by Views On Science-Technology Society (VOSTS, 1989).It is clear, after the analyzes carried out, both in relation to that described by the students as the positioning of the teachers, and even the analysis carried out in the textbook, there is absence, fragmentation in the design and understanding of the STS triad. In this sense, for better contextualize the teachinglearning process, it is necessary to offer different forms of exercises that involve STS, which allow questions, inquiries and reflections the students on various issues involving society in which the same part. To meet this demand was developed as an educational product, a list of examples of exercises.